Super Formula for Soluble C-Type Lectin-Like Receptor 2 × D-Dimer in Patients With Acute Cerebral Infarction - Toshitaka Kamon MD; Hideo Wada MD, PhD; Shotaro Horie MD; Tomoya Inaba MD; Karin Okamoto MD; Katsuya Shiraki MD, PhD; Yuhuko Ichikawa; Minoru Ezaki; Motomu Shimaoka MD, PhD; Akisato Nishigaki MD; Akihiro Shindo MD, PhD; Hideto Shimpo MD, PhD; et al. (Clinical and Applied Thrombosis/Hemostasis, 2024)
Acute cerebral infarction (ACI) includes atherosclerotic and cardiogenic ACI and involves a thrombotic state, requiring antithrombotic treatment. However, the thrombotic state in ACI cannot be evaluated using routine hemostatic examinations. Plasma soluble C-type lectin-like receptor 2 (sCLEC-2) and D-dimer levels were measured in patients with ACI. Plasma sCLEC-2 and D-dimer levels were significantly higher in patients with ACI than in those without it. The sCLEC-2 × D-dimer formula was significantly higher in patients with ACI than in those without it. A receiver operating characteristic curve showed a high sensitivity, area under the curve, and odds for diagnosing ACI in the sCLEC-2 × D-dimer formula. Although the sCLEC-2 and D-dimer levels were useful for the differential diagnosis between cardiogenic and atherosclerotic ACI, the sCLEC-2 × D-dimer formula was not useful. sCLEC2 and D-dimer levels are useful for the diagnosis of ACI and the sCLEC2 × D-dimer formula can enhance the diagnostic ability of ACI, and sCLEC2 and D-dimer levels may be useful for differentiating between atherosclerotic and cardioembolic ACI.